Combination of ultrasonic signal with wavelet analysis for detection of cable degradation / Mohammed Suhaimi Wasi Zainal Ariffin - Zainal Ariffin, Mohammed Suhaimi Wasi (2013)
This paper proposes a technique for identification of insulator's degradation for high voltage cable using ultrasonic technique. The ultrasonic technique signal of the cable was captured using the listening device (Voltage range at 5kV, lOkV and 12.5kV). Then, the sample of ultrasonic signal is transferred to personal computer (PC) using the microphone. These signals are stored in MATLAB workspace for further analysis. The application of Discrete Wavelet Transform (DWT) is used to extract the feature of the ultrasonic signal. From the DWT application, the difference between the normal insulator and degraded insulator of cable could be identified.